A chronology of medieval British history, 1307-1485 - Venning, Timothy, author.
1 online resource
Keywords: "A Chronology of Medieval British History 1307-1485 is a year by year guide to political, military, religious and cultural developments in the states within the British Isles from 1307-1485. Using a chronological framework and dividing the material into separate sections for each state or region each year to allow for easy cross-referencing, A Chronology of Medieval British History 1307-1485 is ideal for students of medieval British and European history"--